Design Sprint Methods for Developing Mobile Learning Application - H Sumual; J Reimon Batmetan; M Kambey (KnE Social Sciences, 2019)
Mobile learning has become an alternative in the learning model. It uses smartphones as a basis for running applications so learning content can be accessed using a smartphone. Many mobile learning applications have been created but only a few are used because the appearance and features are not attractive to users. It is very important to design mobile learning applications specifically because smartphones still have limitations in running various applications. This study aims to examine the techniques of designing mobile learning applications quickly, easily, and cheaply according to users’ needs. The method used in this study is the method of design sprint method which is a fast design model for building applications effectively and efficiently. The results of this study indicate that designing using the Design Sprint Methods model can engineer smartphone-based software easily and quickly. This model can significantly reduce weaknesses in making mobile learning applications. The results of this study also suggest that this model can formulate ideas successfully and creatively to build mobile learning applications. In conclusion, this model is very well used in building mobile learning applications easily and can be implemented quickly.  Keywords: design sprint methods, higher education, mobile learning, prototype, validation